6 Iodo-Delta Lactone Inhibits Angiogenesis in Human HT29 Colon Adenocarcinoma xenograft. - Oglio, Romina (2022)
Introduction: Several studies have shown the antiproliferative effect of iodine and 5-hydroxy-6iodo-eicosatrienoic delta lactone (IL-δ) on diverse tissues. It was demonstrated that moleculariodine (I2) and IL-δ, but not iodide (I-), exerts anti-neoplastic actions in different cancers. Theunderlying mechanism through which IL-δ inhibits tumor growth remains unclear. The aim of thisstudy was to analyze the effect of IL-δ on tumor growth and angiogenesis in human HT29colorectal cancer xenografts.Methodology and Results: HT29 cells were injected subcutaneously into the flanks of nude miceand IL-δ was i.p. injected at a dose of 15 μg three days a week. IL-δ treatment in HT29 xenograftsshowed time-dependent inhibition of tumor growth, decrease of mitosis and PCNA expression(p<0.05), increase of P27 expression and Caspase 3 activity after 18 days of treatment (p<0.05). Toassess tumor Microvessel Densities (MVD), CD31 staining by immunohistochemistry wasanalyzed. IL-δ treatment decreased MVD by 17% and 30% after 18 and 30 days respectively(p<0.05), as well as it decreased VEGF and VEGF-R2 expression (p<0.05). Additionally, ourfindings demonstrated that IL-δ increased VEGF-R1 and Ang-1 mRNA levels (p<0.01).Conclusion: The antitumor efficacy of IL-δ in vivo involves inhibition of cell proliferation as wellas induction of apoptosis. IL-δ has also anti-angiogenic effect associated with VEGF and VEGF-R2downregulation followed by Ang-1 and VEGF-R1 increased expression. High levels of Ang-1would contribute to mature vessel stabilization and maintenance while VEGF-R1 increase wouldproduce anti-proliferative effect on endothelial cells.